The match day use of ultrasound during professional football finals matches. Issue 16 (14th December 2010) - James, Phillip; Barbour, Tim; Stone, Ian
Abstract : Objectives: To describe the use of ultrasound by a professional Australian rules football team in the immediate pregame period to guide local anaesthetic injections, during game time to assess injuries and to guide local anaesthetic injections, and postmatch to assess injuries and to guide therapeutic injections. Methods: The use of match day ultrasound was documented during four finals matches. Local anaesthetic injections were considered effective if players played without pain and experienced no complication from the injection. The results of the diagnostic scans were assessed against subsequent clinical progress and correlation with any follow-up imaging. Therapeutic injections were considered effective if there was clinical improvement and the player was able to play in subsequent weeks without restriction. Results: Pregame, a total of 11 ultrasound guided local anaesthetic injections were performed on eight players, with a further local anaesthetic during a game. All injections achieved good pain relief without any complication. A single diagnostic scan on one player during a game showed no acute muscle tear, the player successfully completed the game. Postgame, a total of four ultrasound guided steroid injections were performed on three players and all players played in the next match. The injections achieved good therapeutic results. The therapeutic injections given immediately postgame, maximised the recovery period available to the players. Conclusions: Ultrasound proved useful in guiding local anaesthetic before and during matches and also therapeutic injections after matches. Ultrasound had a limited role in the assessment of injuries during a game.